Multi-fluid reactive modeling of fluidized bed pyrolysis process - Sharma, Abhishek; Wang, Shaobin; Pareek, Vishnu; Yang, H.; Zhang, D. (Pergamon, 2015)
A multiphase reactive model of biomass pyrolysis process has been implemented by integrating the reaction kinetics of the thermo-chemical decomposition of biomass with the hydrodynamics of the fluidized bed. The model was validated with the experimental data of biomass pyrolysis in the presence of a sand bed. The simulation results were examined to analyze the effect of reactor temperature, superficial gas velocity and biomass particle size on the bed hydrodynamics and product yields. It was found that at temperatures higher than 500 °C, there was a significant conversion of primary tar into NCG (non-condensable gases) due to thermal cracking inside the reactor. However, the increase in superficial gas velocity led to higher concentration of tar due to lower residence time for tar cracking reactions. Any increase in biomass particle size reduced the yield of volatile products due to decrease in the rate of heat transfer, which in turn increased the yield of biochar.